In the dock absurdities of Indian law - Debroy, Bibek (Delhi Konark, 2000)
In the dock indicates that the legal system in India needs reform and such reform has many dimensions. One element is scrapping old statutes, or old sections. Statutes can be Central as well as State-Level. This book is about 3279 Central Statutes, the ea
Keywords: Law-India; Docks-India; Transportaion-Law and legislation